Eliciting children's recall regarding home life and relationships. Issue 4 (2nd October 2018) - Turoy-Smith, Katrine M.; Brubacher, Sonja P.; Earhart, Becky; Powell, Martine B.
Abstract: Child interviews form an important component of custody evaluations. Yet, research on children's responses to questions about home life and relationships is lacking. In the present study, children ( N = 47) aged 6 to 10 years were interviewed about their daily routines and family relationships. Responses to four categories of questions were compared: open and specific questions about routines, and negative and positive aspects of family relationships. Responses were coded for amount of information, informativeness, topic pertinence, and refusals to answer. Results suggested that questions about everyday routines and relationships elicit relevant and informative responses from children. It is suggested that interviewers begin with open-ended questions regarding daily routines to structure family law interviews with children.